Application of iterative software development methodologies for reducing service quality gaps - Galkina, Olga; Yachenko, Vladimir (Proceedings of the 2014 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference : 3-5 February 2014, 2014)
The necessity to satisfy the customers' needs leads to importance of using some methods of IT-service processes organization and monitoring in order to eliminate the possibility of gaps. The paper presents an approach to the application of iterative software development methodologies for reduction of the service quality gaps.